Ecological Divergence Within the Enterobacterial Genus Sodalis: From Insect Symbionts to Inhabitants of Decomposing Deadwood - Tláskal, Vojtěch; Pylro, Victor Satler; Žifčáková, Lucia; Baldrian, Petr (Frontiers in Microbiology, 2021)
The bacterial genus Sodalis is represented by insect endosymbionts as well as free-living species. While the former have been studied frequently, the distribution of the latter is not yet clear. Here, we present a description of a free-living strain, Sodalis ligni sp. nov., originating from decomposing deadwood. The favoured occurrence of S. ligni in deadwood is confirmed by both 16S rRNA gene distribution and metagenome data. Pangenome analysis of available Sodalis genomes shows at least three groups within the Sodalis genus: deadwood-associated strains, tsetse fly endosymbionts and endosymbionts of other insects. This differentiation is consistent in terms of the gene frequency level, genome similarity and carbohydrate-active enzyme composition of the genomes. Deadwood-associated strains contain genes for active decomposition of biopolymers of plant and fungal origin and can utilize more diverse carbon sources than their symbiotic relatives. Deadwood-associated strains, but not other Sodalis strains, have the genetic potential to fix N2, and the corresponding genes are expressed in deadwood. Nitrogenase genes are located within the genomes of Sodalis, including S. ligni, at multiple loci represented by more gene variants. We show decomposing wood to be a previously undescribed habitat of the genus Sodalis that appears to show striking ecological divergence.